The Islamic Regret Minimization Framework: a Decision-Making Approach Based on Maqasid al-Shari'ah - Mohammad Affan; Zaki Ulien Nuha (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
This study examines the alignment and distinctions between the Regret Minimization Framework, a decision-making approach developed by Jeff Bezos, and the principles of Islamic Sharia. While the framework's emphasis on long-term implications and minimizing potential regrets resonates with the Islamic focus on mindfulness, ethical decision-making, and the pursuit of the greater good, key differences also emerge. The Regret Minimization Framework is primarily centered on individual-centric decision-making, whereas Maqasid al-Shariah, which refers to the higher objectives and intents of Islamic law, extends its scope to encompass societal well-being and collective benefit. Utilizing a systematic literature review approach, this study explores the practical applications and implications of the Regret Minimization Framework within the context of Islamic teachings. The findings suggest that while the framework aligns with several principles of Islamic Sharia, its implementation must account for the distinct emphasis of Maqasid al-Shariah on holistic and community-oriented outcomes. The study concludes by recommending further research to explore these synergies and develop practical guidelines for integrating the framework within an Islamic context.